1,550-nm photonic crystal surface-emitting laser diode fabricated by single deep air-hole etch - Kim Myeongeun; Song Ye-Seong; Jeong Lakjong; Lee Tae-Yun; Choi Hyo Seok; Kim In; Lee Myungjae; Jeon Heonsu (Nanophotonics)
Photonic crystal surface-emitting lasers (PCSELs) are promising light sources with numerous advantages, including vertical emission, single-mode operation, and high output power. However, the fabrication of PCSEL devices requires advanced techniques, such as wafer bonding or epitaxial regrowth, to form a photonic crystal (PhC) structure close to the central waveguide layer. This process is not only complicated but also necessitates multiple semiconductor epitaxies, which reduces fabrication yield and increases manufacturing costs. In this study, we introduce a simpler method for fabricating PCSELs that requires only a single dry-etch run on any standard edge-emitting laser diode epistructure. The key challenge of creating an array of PhC air holes deep enough to reach the waveguide layer is addressed through high-temperature, high-plasma-density dry etching. PCSEL devices fabricated using this method lased in single mode at a threshold current density as low as ∼0.8 kA/cm2, which is comparable to or better than previously demonstrated devices. Our results offer a cost-effective, high-yield approach to PCSEL fabrication.